Can Expectant Management Gives Better Outcome than Immediate Delivery in Females Presenting with Preterm Premature Rupture of Membrane Close to Term - Shagufta Jabbar, Ghazala Iftikhar, Fariha Arshad, Amna Asif, Naila Khawar, Sadaf Kashif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcome of expectant management versus immediate delivery in females with preterm premature rupture of membrane close to term. Study Design: Randomized controlled trial Place and Duration of Study: Department of Obstetrics & Gynaecology Unit III, Fatima Memorial Hospital Lahore from 20th June 2018 to 20th December 2018 Methodology: Three hundred females were included through emergency. They were divided in two groups; females of group A managed conservatively and females of group B were induced for delivery and immediate delivery was conducted. After delivery in both groups, outcome was recorded i.e. neonatal distress, poor Apgar score or NICU admission. Results: The mean age of group A was 27.53±4.99 years and group B was 25.81±4.92 years. The mean gestational age of group A was 33.92±1.41 weeks and group B was 33.88±1.40 weeks. In group A there were 28 (18.7%) women with parity 1, 40(26.7%) with parity 2, 42 (28%) with parity 3 and 40 (26.7%) with parity 4 whereas in group B there were 28(18.7%) women with parity 1, 40 (26.7%) with parity 2, 42 (28%) with parity 3 and 40 (26.7%) with parity 4. In group A there were 54 (36%) women with normal BMI, 44 (29.9%) were overweight and 52 (34.7%) were obese while in group B there were 63 (42%) women with normal BMI, 38 (25.3%) were overweight and 49 (32.7%) were obese. There was no significant (P=0.329) association between neonatal distress and study groups and also no significant (P=0.202) association between poor APGAR score and study groups. Conclusion: Incidence and rate of neonatal distress in complicated pregnancies by PPROM within 34 and 37 weeks of gestation is very low